Design and Development of Treadmill Controller with Wireless Mobile Health Monitoring System - Sharma, Gaurav; Pandey, Amit (International Journal of Computer Sciences and Engineering, 2025)
Humans used to workouts to burn calories to stay physically fit. For this purpose, Treadmills are extensively used inside gym as well as at home. The mechanical work done on the treadmill can be utilized to generate electrical power with minor machine modifications. This paper present a methodology to generate energy from various exercise equipment e.g. treadmill, bicycle. A microcontroller based automated electronic power controller has been developed. It controls and monitor generated power up to the storage device. MPPT algorithm along with CUK converter is implemented for better power efficiency. An independent health monitoring system has also been developed. It is a microcontroller based device which measures various health characteristics of the user. It also maintain database of health status reports for future use. For instant health status routine GSM based mobile SMS service used along with UART based PC communication. The designed system stores power generated while workouts and it also measures user health status continuously during workouts.